The Sports Connection, integrated simulation : Microsoft office - VanHuss, Susie H.; Forde, Connie (Cincinnati, OH : South-Western Educational, 1999)
This book is about: Getting organized; researching; Reporting; Managing routline tasks; Planning the Grand opening; Designing publicity pieces; Communicating; and Managing information.
Keywords: Microsoft Office; Management; Data processing; Sports facilities; Microsoft Office; Sports facilities -- United States -- Management -- Computer simulation; Sports facilities -- United States -- Management -- Data processing